2020
DOI: 10.2147/oarrr.s262428
|View full text |Cite
|
Sign up to set email alerts
|

<p>Association of Silicone Breast Implants, Breast Cancer and Anti-RNA Polymerase III Autoantibodies in Systemic Sclerosis: Case-Based Review</p>

Abstract: Some case reports and small case series of patients with silicone breast implant (SBI) have reported the development of systemic sclerosis (SSc) many years later, despite conflicting evidence of this association in the literature. Recently, patients with SSc and anti-RNA polymerase III antibodies positivity have been associated with previous silicone implants and/or breast cancer, showing clinical features that differ from the classic SSc, such as rapid and diffuse cutaneous involvement and scleroderma renal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
3
0
1
Order By: Relevance
“…With the increasing use of silicone breast implants, it has been postulated that silicone could also lead to an increase in autoimmunity by creating a chronic inflammatory state and/or functioning as an adjuvant, thus lowering the threshold for the loss of self-tolerance. Separate case studies from Italy confirmed a higher frequency of silicone breast implants [13] and a higher risk for rupture [14] specifically in patients with ARA-positive SSc. Although smoking has been identified as a potential trigger for autoimmunity in general [15], and a risk factor for worse prognosis in patients with SSc [16], ATA were found to be negatively associated with smoking (OR 1.77, 95% CI 1.04–2.99, P = 0.034) [17].…”
Section: Triggers/initiating Eventsmentioning
confidence: 84%
See 1 more Smart Citation
“…With the increasing use of silicone breast implants, it has been postulated that silicone could also lead to an increase in autoimmunity by creating a chronic inflammatory state and/or functioning as an adjuvant, thus lowering the threshold for the loss of self-tolerance. Separate case studies from Italy confirmed a higher frequency of silicone breast implants [13] and a higher risk for rupture [14] specifically in patients with ARA-positive SSc. Although smoking has been identified as a potential trigger for autoimmunity in general [15], and a risk factor for worse prognosis in patients with SSc [16], ATA were found to be negatively associated with smoking (OR 1.77, 95% CI 1.04–2.99, P = 0.034) [17].…”
Section: Triggers/initiating Eventsmentioning
confidence: 84%
“…Overview of autoantibody development in SSc. Viral infections, silica, and malignancy have recently been studied as potential triggers for autoantibody development [4–8,10–14,18–20,21 ▪ ]. These initiating events lead to a breach of tolerance at the level of DC:T cell interactions, which may be influenced by SSc-associated motifs in the DRB1 peptide-binding groove [26 ▪▪ ,27].…”
Section: Introductionmentioning
confidence: 99%
“…Several case studies link silicone breast implants with increased incidence of ARA positive scleroderma and silicone breast implant rupture has been implicated in induction of ARA positive SSc [44,45].…”
Section: Antigen Triggersmentioning
confidence: 99%
“…На сегодняшний день индивидуальные принципы скрининга РМЖ у пациенток с ССД не разработаны и, вероятно, соответствуют таковым в общей популяции. Особенно важно в данной ситуации перед назначением МГТ определять анти-RNP III, особенно у пациенток с диффузной формой ССД [65].…”
Section: риск развития рака молочной железы при системной склеродермииunclassified